Appraisal of the Achievements of Sustainable Development Goals and the Role of Public-Private Partnerships in Water, Sanitation, and Hygiene Projects in Plateau State, Nigeria - Andesikuteb Yakubu Ali; Clement Yakubu Giwa; Ezra Lekwot Vivan; Tony Aku Amba (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
This study appraises the role of SDGs and the provision of water supply, sanitation, and hygiene (WASH) facilities in Plateau State, Nigeria, from 2015 to 2020. It utilized both primary and secondary data sources. The primary data were obtained through stakeholder interviews conducted on the Engineering staff of the SDGs office in Jos, Plateau State, the users of these projects were randomly sampled across the State and field observation of the authors. The secondary data, on the other hand, were obtained from the reports and other documents of the same SDGs office. In this study, frequency tables and maps were used in presenting and analysing the results. The study also found that the WASH projects were executed for social, political, and to some extent economic reasons and are not sustainable due to the inability of the government to carry the end users along from execution stages. Results also show that these projects are not evenly distributed across wards, districts, and Local Government Areas in Plateau State due to the presence and agglomeration of some of them in especially the metropolitan places and enumerated the benefits of these WASH projects to users to include reduced distance to water source, time savings, reduction in rates of open defecation and reduction in diseases rate. It is concluded that some level of government- community collaborations should be fostered to enable the projects become sustainable in delivering their gains in all locations of the State. The study recommends, among other things, the replication of these projects within communities across the state, the involvement of the communities at stages of execution, and the establishment of a mechanism for the sustainability of the projects.